Does Foreign Direct Investment Reduce Growth Government Debt? - Dina Hendiyani; Zainuddin Iba (PT Inovasi Pratama Internasional, 2023)
The problem of fiscal deficits in the Indonesian economy has prompted the government to increase debt as a solution to reduce the deficit. Debt withdrawal in the long term without the support of an increase in state revenues has had a negative impact. Government debt increased sharply. Efforts to increase state revenue through tax collection in post-Covid 19 economic conditions that have not yet recovered will only reduce economic activity. This requires efforts to suppress government debt growth amidst a fiscal deficit. This study aims to analyze the effect of foreign direct investment, inflation and the exchange rate on government debt. Foreign direct investment is believed to be a source of financing that cannot be made through state revenue. Especially public infrastructure financing. The study concluded that it was found: foreign direct investment, inflation, and the exchange rate had a significant effect on government debt. Thus, government efforts are needed to encourage the growth of foreign direct investment, through policies that are oriented towards increasing foreign direct investment.